The Benefit Sanction: A Correctional Device or a Weapon of Disgust?. (March 2020) - Redman, Jamie
The benefit sanction is a dominant activation policy in Britain's 'welfare-to-work' regime. While policymakers believe in their necessity to correct behaviour, research shows benefit sanctions cause additional harm to Britain's marginalised groups. Drawing upon a small-scale qualitative study, this article first navigates new territory, mapping the ways stigma emerges from the state – channelled through the benefit sanction – and manifests in the lives of sanctioned claimants. Acknowledging wider evidence, the sanction is then argued to have failed as a correctional device. Rather, taking into account Britain's current politico-economic climate, the sanction appears as a weapon used to incite negative emotion in an attempt to police the boundaries of the labour market, while frequently abandoning some of the UK's most vulnerable citizens.